Perkembangan Motorik Kasar Anak Dengan Tes DDST Siswa TK-B Di Kecamatan Ajibarang (Universitas Negeri Semarang, 2021)
The purpose of this study is to find out the level of development of rough motor kindergarten students in Ajibarang Sub-district. This research is quantitative research. The population in this study is all kindergarten students in Ajbarang Sub-district, because of the large number, so researchers did a certain classification (Purposive Sampling) to determine the sample to be studied. The results of the study were as follows, mostly in the normal category with the number of students taking the test of 112 students consisting of 94 children with normal results (83.9%), as many as 18 children with suspect results (16.1%). The results showed that the level of motoric development of rough students belongs to a good category, but attention to the development of the child's rough motoik must still be done so that the child grows and develops optimally and in adulthood can support his performance.